The value of endoscopy and cone beam computed tomography angiography in studying the arterial system in vicinity to guttural pouch horses - Jais, Haniza (2017)
Guttural pouches are the large diverticula of the eustachian tubes that connect the pharynx to the middle ear. It is a unique structure in equine as it is anatomically located very closely to other important structures such as internal carotid artery, maxillary artery, external carotid artery, glossopharyngeal nerve, and hypoglossal nerve. These structures are important in the event of guttural pouch mycosis as the damage can cause neurological deficit and severe haemorrhage, which may be fatal to the horse. Hence, a study was conducted to determine the value of using cone beam computed tomography angiography in studying the arterial system in vicinity to the guttural pouch. Two retired horses were euthanized humanely for reasons or problems unrelated to the guttural pouches were used for this study. Iodine based contrast media (Iomeprol) was injected via common carotid arteries to highlight the arteries of the cadaveric heads. Based on the computed tomography angiography images, the important arteries in vicinity to the guttural pouch can be recognized and observedin three different plane, which are the transverse plane, the sagittal plane, and the dorsal plane. Even though there are several limitations in using this method, computed tomography study of the guttural pouch and the important arteries provided excellent imaging of the anatomical pathways of the associated arteries in relation to the pouch.